Delay in the Distribution of Inheritance to Women in Temanggung - Rokhmat2; Alvi Yaturohmaniyah (Jurnal Syariah, Hukum, dan Ekonomi Islam, 2024)
This study examines the practice of delaying the distribution of inheritance to female heirs in Dusun Kauman, Kemiriombo Village, Temanggung District, from the perspective of Islamic inheritance law. In Islamic jurisprudence, inheritance is a mandatory right that must be fulfilled immediately after the death of the deceased, following the settlement of debts and wills, as stipulated in the Qur’an and the Sunnah. However, empirical evidence shows that inheritance distribution in rural communities is often postponed due to social, economic, and customary considerations. This research employs a qualitative field research approach. Primary data were collected through in-depth interviews, observation, and documentation involving female heirs, religious leaders, and village officials. Secondary data were obtained from the Qur’an, Hadith, classical Islamic legal texts, and relevant scholarly literature. Data analysis was conducted using the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing, with source triangulation applied to ensure the validity of the findings. The findings indicate that the delay in inheritance distribution is primarily influenced by social concerns for family harmony, economic dependence on inherited agricultural land, and patriarchal cultural norms that subordinate women’s inheritance rights. From the perspective of Islamic law, such delays are only permissible if they are genuinely based on collective agreement, do not eliminate or diminish women’s rights, and serve clear public benefit (maṣlaḥah). Otherwise, they constitute a violation of Islamic principles of justice and the objectives of Islamic law (maqāṣid al-sharīʿah), particularly the protection of property and lineage. This study highlights the tension between Islamic normative law and customary practices within a plural legal system and emphasizes the need for legal awareness, religious guidance, and institutional support to ensure gender justice and legal certainty for female heirs.